Comparison of SPWM and SVPWM Based Closed Loop Speed Control of BLDC drive (International Journal of Engineering and Computer Science, 2018)
Brushless DC Motor is a highly popular motor because of their  high reliability; high efficiency , good dynamic response and very low maintenance so Demand for small & highly reliable motors is increasing. In the BLDC motor at low speed  controlling the stator phase current  is more effective peed but at high speed range  ripple in torque reduction is not reliable in conventional technique. The two techniques sinusoidal PWM and Space vector PWM are studied for close-loop speed control of a BLDC  Motor. MATLAB/Simulink simulation model is done for SPWM and SVPWM control scheme. The results of simulation shows the  advantage of less harmonic distortion and lower switching of SVPWM is better than that of SPWM technique in losses the speed control of BLDC motor.